2022
DOI: 10.1108/bfj-05-2021-0574
|View full text |Cite
|
Sign up to set email alerts
|

Application of the technology acceptance model to food delivery apps

Abstract: PurposeThis study explores food delivery app users and technology acceptance model as a theoretical underpinning. This study thus investigated the determinants of usefulness, ease of use and intention to use for food delivery app service.Design/methodology/approachThe variables of delivery time, diverse menu, quarantine, review quality and ease of use are employed as determinants of usefulness. The antecedents of ease of use are easy registration and easy payment. This study also examined the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 73 publications
(224 reference statements)
3
17
0
Order By: Relevance
“…the four basic constructs in the theory of planned behaviour model) positively predicted consumers' intentions to continue to use food delivery apps. Similarly, Lee et al (2023) adopted the technology acceptance model to explore consumers' intention to use OFODSs and found that ease of use and usefulness positively influence intention to use apps. This result is in line with Gani et al (2021), who found that information and food service attributes influenced the perceived usefulness of OFODSs and shaped respondents' intention to use them.…”
Section: Ofods Quality and Customer Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…the four basic constructs in the theory of planned behaviour model) positively predicted consumers' intentions to continue to use food delivery apps. Similarly, Lee et al (2023) adopted the technology acceptance model to explore consumers' intention to use OFODSs and found that ease of use and usefulness positively influence intention to use apps. This result is in line with Gani et al (2021), who found that information and food service attributes influenced the perceived usefulness of OFODSs and shaped respondents' intention to use them.…”
Section: Ofods Quality and Customer Expectationsmentioning
confidence: 99%
“…the four basic constructs in the theory of planned behaviour model) positively predicted consumers' intentions to continue to use food delivery apps. Similarly, Lee et al. (2023) adopted the technology acceptance model to explore consumers' intention to use OFODSs and found that ease of use and usefulness positively influence intention to use apps.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It entails transparent information sharing to make consumers feel assured. Specifically, researchers have unveiled OFD consumers’ desires for real-time tracking, transparent and high-quality online reviews (Cho et al ., 2019; Lee et al ., 2023). Therefore, the assurance of OFD service is operationalized as follows:ASSUR1 – Real-time GPS tracking: consumers are enabled to monitor the location of food delivery rider and the estimated delivery time.ASSUR2 – Food reviews: consumer reviews of the food and restaurant chains are available.ASSUR3 – Rider reviews: consumer reviews of food delivery riders are available.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…OFD platforms have also been diversifying their services to cater to consumers’ personalized requirements. Although often omitted by research conducted in other regions, the multitude of payment options is found to be important for Asian consumers (Lee et al ., 2023; Pandey et al ., 2022). Singapore, our research area, is characterized by diversified payment methods (Statista, 2022a).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation